DELIMITATION OF HOMOGENEOUS ZONES IN VINEYARDS USING GEOSTATISTICS AND MULTIVARIATE ANALYSIS OF DIFFERENT VEGETATION INDICES - Costa, Bruno R. S. [UNESP]; Oldoni, Henrique [UNESP]; Rocha Junior, Romero C.; Bassoi, Luis H. (Soc Brasil Engenharia Agricola, 2019)
Vegetation indices (VIs) are quantitative measures used to describe the distribution and spatial variability of the vegetation cover of natural or cultivated areas. The aim of this study was to delimit homogeneous zones (HZs) of different VIs using geostatistics and multivariate analysis in order to identify vegetation patterns in Cabernet Franc and Cabernet Sauvignon vineyards. The evaluation was performed in two vineyards in the municipality of Espirito Santo do Pinhal in the state of Sao Paulo, Brazil. Reflectance (rho) was measured at three wavelengths of the electromagnetic spectrum (670, 730, and 780 nm) at canopy height in georeferenced points along planting rows using the Crop Circle ACS-430 active sensor. Nine VIs were calculated based on the ratios between the rho values. Geostatistical data analysis allowed the spatial prediction of VIs by ordinary kriging interpolation. Principal component analysis and fuzzy k-means clustering were applied for HZs delimitation and the optimal number of zones was defined according to cluster validity functions. Despite the variations of the VIs spatial distribution patterns, the multivariate analysis resulted in a representative categorization of the grapevine vegetative vigor and delimitation of HZs for this characteristic. This was validated according to the observed significant differences between VIs.
Keywords: Vitis vinifera L.; canopy density; agricultural instrumentation